Kinetic and Mechanism of Electron-Transfer Reactions: Silver (I) Catalyzed Oxidation of L-Ascorbic Acid by Peroxodiphosfate in Acetate Buffers - K. Soni, Narendra; Sailani, Riya; L. Khandelwal, Chandra; D. Sharma, Prem (Current Catalysis, 2014)
The kinetics of silver (I) catalyzed oxidation of l-ascorbic acid (H2A) by peroxodiphosfate (PDP) in acetate buffers has been studied. Triple distilled water was employed to eliminate suspected trace metal-ion catalysis of Cu (II) or Fe (III). The kinetics was monitored ceremetrically and the rate has been found to be independent of substrate concentration. A plausible reaction mechanism has been suggested. Results were analysed graphically in view of complex rate equation. The role of the catalyst has been via AgI/AgII redox cycle, Ag (II) confirming the presence of by the addition of 2,2’-bipyridyl where brown-orange color of AgI(bipy)2 complex of transient life time was observed.
Keywords: mechanism